Diarrhea in Yemeni children under five: A multi-level analysis of population-based surveys, 1991-2022. - Zahir M Tag; Laith J Abu-Raddad; Hiam Chemaitelly (PLoS Neglected Tropical Diseases)
Background Yemen, grappling with a protracted humanitarian crisis, armed conflict, forced displacements, and economic hardship, faces a burden of childhood diarrhea. This study aimed to assess diarrhea prevalence, trends, and underlying factors among children under five in this population. Methods Data were sourced from the population-based, nationally representative Yemen Demographic and Health Surveys (1991 and 2013) and Multiple Indicator Cluster Surveys (2006 and 2022). A three-level random-effects logistic regression model was used to identify risk factors, with clustering effects analyzed at both the neighborhood and household levels. Results The study included 6,451 children under five in 1991, 3,778 in 2006, 15,278 in 2013, and 19,501 in 2022. Diarrhea prevalence was 34.8% (95% CI: 32.6-37.1%) in 1991, 33.6% (95% CI: 31.6-35.6%) in 2006, 31.4% (95% CI: 30.1-32.7%) in 2013, and 37.4% (95% CI: 36.2-38.7%) in 2022. The adjusted odds ratios (aORs) for diarrhea were twice as high for children aged 12-23 months compared to those aged less than 12 months and decreased steadily with increasing age. Females had 15% lower odds of diarrhea than males. The aORs were higher for households in North Yemen, those without water on premises, or those with unimproved toilet facilities, but lower for households with more than five members and those in the highest wealth quintile. Between-cluster differences decreased between 1991 and 2006 but increased between 2013 and 2022. Disparities were much more pronounced between households than across neighborhoods. Conclusions Using a three-level modeling approach and analyzing trends over a three-decade period, this study revealed a persistent and worsening burden of childhood diarrhea in Yemen, with prevalence more than twice the global average. Urgent action is needed to improve water and sanitation infrastructure and implement targeted programs to reduce diarrhea prevalence.